Hedging capabilities of bitcoin is it the virtual gold? - Anne Haubo Dyhrberg (University College Dublin, UCD School of Economics, 2015)
This paper sets out to explore the hedging capabilities of bitcoin by applying the asymmetric GARCH methodology used in investigation of gold. The results show that bitcoin can clearly be used as a hedge against stocks in the Financial Times Stock Exchange Index. Additionally bitcoin can be used as a hedge against the American dollar in the short-term. Bitcoin thereby possess some of the same hedging abilities as gold and can be included in the variety of tools available to market analysts to hedge market specific risk.
Keywords: 330; Bitcoin; Risk Management; Gold; Hedging